PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY (CSR) PERBANKAN SYARIAH DI INDONESIA: STRATEGI ATAU SOSIAL? - Maharani, Astrid (Jurnal Ilmiah Akuntansi Indonesia, 2016)
The development of Islamic banking in Indonesia is also accompanied by the development of one of the issues which arise that disclosure of CSR activities in Islamic?banking. The magnitude of the expectations of the stakeholders and the public rushes to Islamic banking and CSR disclosure in their annual reports, although there is no standard in Indonesia, which standardize the disclosure of CSR in Islamic banking. Islamic banking CSR disclosure, this is an Islamic banking efforts to improve accountability, transparency, and maintaining partnerships with stakeholders, so that later it is what motivates the Islamic banking to make ?best effort? for the CSR disclosure and not just because of what would be obtained by islamic banks after revealing CSR.Keywords: CSR Activities, CSR Disclosure, Islamic Banking, Mo